Neuromuscular profile of top-level women kayakers assessed through tensiomyography - Garcia-Garcia, O.; Cancela-Carral, J. M.; Huelin-Trillo, F. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study is to assess the contractile properties and the lateral symmetry percentages of trapezius, deltoideus, and latissimus dorsi muscles of top-level female kayakers [FKs]) and to determine the gender influence and the specific training in the assessed parameters. Twenty-one volunteers participated in this study, who were stratified into 3 groups: 7 top-level FKs, 4 top-level men kayakers (MKs), and 10 physically active female non-kayakers (FNKs), and they have been assessed through tensiomyography (TMG). Reliability of the TMG assessment was tested by calculating intraclass correlation coefficient reliabilities, and all the values obtained were over 0.8. A t-test (p = 0.05), a 1-factor analysis of variance (p = 0.01), and Cohen's d effect sizes were implemented, and we used the algorithm of TMG-BMC tensiomyography to determine the lateral symmetry percentages. The results show that FKs and MKs differ only in the lower reaction time that FKs obtain when contracting their trapezius muscle (19.5%; p = 0.008; d = 2.13). However, FKs present >34.4% of time contraction (p = 0.003; d = 1.8) in their latissimus dorsi muscle than FNKs. Also, FKs have >123.7% of time contraction (p = 0.009; d = 1.5), >11.3% of time reaction (p = 0.01; d = 1.5), >34.8% of maximum radial displacement (p = 0.01; d = 1.35), and <20.4% of lateral symmetry (p = 0.006; d = 1.6) in their trapezius than FNKs. In conclusion, the specific training seems to have a significant influence on the FK's neuromuscular profile compared with FNKs.